Assessment of epidemiologic, operational, and sociopolitical domains for mainstreaming nutrition - Menon, Purnima; Frongillo, Edward A.; Pelletier, David L.; Stoltzfus, Rebecca J.; Ahmed, A. M. Shamsir; Ahmed, Tahmeed (SAGE Publications, 2011)
Although undernutrition impacts a range of short- and long-term outcomes, nutrition often has low priority on global and national development policy agendas because of overemphasis on technical solutions without adequate consideration of contextual and political factors. An approach is needed for strategic development of nutrition agendas that embraces the contexts influencing policy and program planning and implementation, while addressing salient causes of undernutrition. We describe a simple, comprehensive assessment approach to enable development of sound nutrition strategies and well-grounded effective and appropriate actions for nutrition in a given context. The conceptual framework for this assessment approach incorporates three domains, each essential for defining strategic actions for nutrition: epidemiologic, pertaining to the nutritional situation and the evidence about the efficacy and effectiveness of nutrition interventions; operational, pertaining to coverage, quality, and utilization of nutrition-related interventions and programs as well as capacities, opportunities, and constraints to improving these; and sociopolitical, pertaining to social, political, cultural, and organizational factors at various levels, which may enhance or inhibit efforts to create positive changes in policies and programs. The domains are interlinked, and the sociopolitical domain often underlies the other two domains. Using this framework can reveal important insights for the nutrition policy agenda that were hitherto not considered explicitly in efforts to advance nutrition. This is highlighted in an example from Vietnam and through other papers in this Supplement. Use of this three-domain assessment framework can greatly aid development of feasible and actionable nutrition strategies that are grounded in epidemiologic, operational, and sociopolitical realities.